PELAKSANAAN PEMOTONGAN, PENYETORAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 4 AYAT (2) ATAS PERSEWAAN TANAH DAN BANGUNAN OLEH PT HERLINA INDAH MASA PAJAK JANUARI SAMPAI DENGAN JUNI TAHUN 2015 - Aji Prasetyo; Toni Triyulianto; Nenden Apisa (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2017)
Final Income Tax is an income tax whose approval is final (ending) so that it cannot be credited (deducted) from the total income owed at the end of the tax year. The purpose of this study is to find out how the implementation of obligations as Taxable Entrepreneurs on Income Tax in 2015 is in accordance with applicable regulations or not. The method used in collecting data is by interviewing, observing and citing documents in order to find out the implementation of deduction and depositing of income tax by PT Herlina Indah from January to June 2015. According to observations as Taxable Entrepreneurs (PKP). PT Herlina Indah has carried out its obligations, namely cutting, depositing and reporting Income Tax Article 4 Paragraph (2). It was concluded that the Implementation of Obligations as Taxable Entrepreneurs on Income Tax Article 4 paragraph (2) for Land and Building Rental by PT Herlina Indah for the tax period of January to June 2015 was in accordance with the applicable tax provisions